Termite sensitivity to temperature affects global wood decay rates - Zanne, Amy E; Flores-Moreno, Habacuc; Powell, Jeff R; Cornwell, William K; Dalling, James W; Austin, Amy T; Classen, Aimée T; Eggleton, Paul; Okada, Kei-Ichi; Parr, Catherine L; Adair, E Carol; Adu-Bredu, Stephen; et al. (Science (New York, N.Y.), 2022)
Deadwood is a large global carbon store with its store size partially determined by biotic decay. Microbial wood decay rates are known to respond to changing temperature and precipitation. Termites are also important decomposers in the tropics but are less well studied. An understanding of their climate sensitivities is needed to estimate climate change effects on wood carbon pools. Using data from 133 sites spanning six continents, we found that termite wood discovery and consumption were highly sensitive to temperature (with decay increasing >6.8 times per 10°C increase in temperature)-even more so than microbes. Termite decay effects were greatest in tropical seasonal forests, tropical savannas, and subtropical deserts. With tropicalization (i.e., warming shifts to tropical climates), termite wood decay will likely increase as termites access more of Earth's surface.
Keywords: Carbon Cycle; koloběh uhlíku; Isoptera; globální oteplování; Global Warming; zvířata; Forests; Temperature; tropické klima; lesy; Wood; Tropical Climate; teplota; dřevo; Animals